Distress Proneness of Farmers in Agriculturally Developed Cauvery Delta Zone of India - A. Pouchepparadjou; M. Umamageswari; R. Jayakumara Varadan; S. Parthasarathi; D. Cathrine (Agricultural Research, 2026)

Effective forecast diagnostics for predicting extreme rainfall events: A statistics-based approach - Snehlata Tirkey; Tanmoy Goswami; Malay Ganai; M K R Phani; Medha Deshpande; Parthasarathi Mukhopadhyay; D R Pattanaik (Journal of Earth System Science, 2025)

Interactions between subpolar and subtropical jet streams lead to extreme rainfall events over the North Indian Subcontinent in June 2013 and July 2023 - Dipanjan Dey; Ligin Joseph; Arkaprava Ray; Robert Marsh; Nikolaos Skliris; Andrew G. Turner; D. C. Ayantika; Parthasarathi Mukhopadhyay; Arun Chakraborty; Sourav Sil (Climate Dynamics, 2025)
North Indian Subcontinent (NIS) is prone to disastrous and life-threatening floods during the summer monsoon period primarily due to its close proximity with the Himalayan foothills. Indian Meteorological Department (IMD) reported that during June 13–19, 2013, the Uttarakhand state in North India experienced a cumulative total of 322 mm rainfall, a 847% weekly departure against the long-term average rainfall (1971–2020) of 34 mm. After a decade, another state in the same region, Himachal Pradesh, received an unprecedented 223 mm of rainfall in just 4 days, viz 7–11 July 2023, a 436% deviation from the cumulative climatological rainfall of 41.6 mm for 4 days (July 7–11). It is shown that the atmospheric water vapor is transported towards NIS by two monsoon low pressure systems during the June 2013 event. In contrast, during the July 2023 flood, the monsoon trough shifted southward, resulting in the moisture transport pathway predominantly over the northern Indian Ocean. In conjunction, it was shown through upper-level air tracing that southward movement of the subpolar jet stream creates a trough in the subtropical jet stream, which intrudes along the western boundary of NIS, leading to upper-level divergence. This pattern was observed in both flood events. By leveraging the mass-conserving nature and unique capability of a Lagrangian tracing model to track atmospheric water backward in time, our novel analysis of the 2023 flood reveals that two evaporative sources near Madagascar and the western Indian Ocean were key contributors, and inland evaporation played a comparatively lesser role as compared to the 2013 case. The Bay of Bengal served primarily as a vapor transport pathway rather than a direct moisture source for both events. This novel Lagrangian approach, which exposes separate drivers of extreme monsoon rainfall, upstream and at lead times of days-weeks, has the potential to be used more extensively and operationally.

Performance of a novel NWP–AI hybrid lightning early warning system over Indian Subcontinent - Rituparna Sarkar; Parthasarathi Mukhopadhyay; Sunil D Pawar (Journal of Earth System Science, 2025)

Epigenetic modulation and apoptotic induction by a novel imidazo-benzamide derivative in human lung adenocarcinoma cells - Amrutha Arjunan; Sankar Pajaniradje; Arul Prakash Francis; Srividya Subramanian; Sathyapriya Chandramohan; D. Parthasarathi; Ayyiliath M. Sajith; M. Syed Ali Padusha; P. P. Mathur; Rukkumani Rajagopalan (DARU Journal of Pharmaceutical Sciences, 2021)

Evaluation of convective parameterization schemes in simulation of tropical cyclones by Climate Forecast System model: Version 2 - Radhika D Kanase; Medha S Deshpande; R P M Krishna; Parthasarathi Mukhopadhyay (Journal of Earth System Science, 2020)

A highly efficient precatalytic system (XPhos-PdG2) for the Suzuki–Miyaura cross-coupling of 7-chloro-1H-pyrrolo[2,3-c]pyridine employing low catalyst loading - Bhaskaran Savitha; Eeda Koti Reddy; D. Parthasarathi; Rajeesh Pakkath; Ranjith Pakkath Karuvalam; C. S. Ananda Kumar; K. R. Haridas; M. Syed Ali Padusha; Ayyiliath M. Sajith (Molecular Diversity, 2019)

Analyzing Toxicity Through Electrophilicity - D. R. Roy; U. Sarkar; P. K. Chattaraj; A. Mitra; J. Padmanabhan; R. Parthasarathi; V. Subramanian; S. Van Damme; P. Bultinck (Molecular Diversity, 2006)